Planning and Sustainability: an analysis of the management of tourism 2006-2008 representations from the terms of Palm, CVI and Mariculture in the city of Valença / Bahia - Castro, Fernanda Meneses de Miranda; Midlej, Moema Maria Badaró Cartibani (Revista Turismo em Análise, 2013)
The objective of this research was to examine how representations of words palm, CVI and mariculture are contemplated in the planning of the tourist city of Valença from the perception of the social actors involved in the tourism sector. The research was divided into two stages: at first it was held that literature was the literature review. In the second phase was conducted descriptive and explanatory research using primary and secondary data, where we seek to interpret, as the technique of content analysis (BARDIN, 2004), where the image socio-economic and cultural representatives of the tourism sector has on these terms in the development of tourism in the city. The results indicated difficulties in integrating the core economic activities (considered structural) as tourism and planning, issues of ideological (or superstructure), such as citizenship, identity, topophilia, social responsibility, ethics and sustainability (ORTIZ, 1998). The research concluded that the process of structuring of tourism based on participation and integration of public and private sectors and the local community, can bring more effective results and consistent with the reality of the region.